Lithium battery cover plate and production process thereof
Patent Information
- Application Number
- CN202611038993.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-14
- Publication Date
- 2026-10-16
AI Technical Summary
当绝缘件在装配、振动、热循环或电解液腐蚀作用下发生偏移、破损或老化时,容易导致金属盖板与导电部件之间形成异常导电通路,引发短路风险
[0017] Compared with existing technologies, the advantages of this invention are as follows: 1. This invention uses a plastic component and a metal component surrounding the plastic component to form a lithium battery cover. The metal component is used for welding and fixing to the battery casing, while the plastic component provides internal insulation and electrolyte sealing. Through this structure, the welding support function and insulation sealing function, which are simultaneously performed by the metal component in traditional metal cover plates, are separated. This allows the metal component to primarily meet the requirements for welding strength and structural support, while the plastic component primarily meets the requirements for insulation and electrolyte sealing. This reduces the risk of short circuits caused by insulation component misalignment, damage, or aging, thus improving the safety of the battery cover.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium battery technology, specifically to a lithium battery cover plate and its manufacturing process. Background Technology
[0002] Lithium-ion batteries have been widely used in new energy vehicles, energy storage systems, consumer electronics and power tools due to their advantages such as high energy density, long cycle life and low self-discharge rate.
[0003] Lithium battery covers are typically placed at the opening of the battery casing to seal the internal space of the battery and to support components such as terminals, insulation parts, explosion-proof structures, or liquid filling structures.
[0004] The main body of a lithium battery cover is generally made of metal such as aluminum alloy through stamping. However, metal materials are inherently conductive, and additional insulating components are necessary to isolate the cover from conductive parts such as terminals and current collectors. When the insulating components shift, break, or age under the influence of assembly, vibration, thermal cycling, or electrolyte corrosion, an abnormal conductive path can easily form between the metal cover and the conductive parts, leading to a short circuit risk.
[0005] Based on this, the present invention designs a lithium battery cover plate and its manufacturing process to solve the above problems. Summary of the Invention
[0006] In view of the above-mentioned shortcomings of the existing technology, the present invention provides a lithium battery cover plate and its manufacturing process.
[0007] To achieve the above objectives, the present invention provides the following technical solution: A lithium battery cover includes a plastic part and a metal part surrounding the outside of the plastic part. The plastic part is used to provide internal insulation and electrolyte sealing, and the metal part is used to weld and fix it to the battery casing. The plastic part comprises the following raw materials in parts by weight: 100 parts of semi-aromatic polyamide, 15-22 parts of polyphenylene sulfide, 5-18 parts of polyetherimide resin, 0.5-3 parts of maleic anhydride graft compatibilizer, 2-8 parts of talc and boehmite composite modified powder, 0.3-1.5 parts of hydrolysis resistant agent, 0.2-0.8 parts of antioxidant, and 0.2-1 parts of lubricant.
[0008] Furthermore, the metal component comprises the following raw materials in weight percentages: Mg: 0.50-0.80%, Si: 0.20-0.40%, Fe: 0.11-0.22%, Cu: 0.05-0.10%, Mn: 0.06-0.12%, Sc: 0.03-0.05%, Zr: 0.02-0.05%, Ti: 0.01-0.03%, B: 0.001-0.005%, Nb: 0.01-0.03%, with the balance being Al and unavoidable impurities.
[0009] Furthermore, the hydrolysis-resistant agent is carbodiimide; the antioxidant is at least one of antioxidant 1098 and antioxidant 168.
[0010] Furthermore, the lubricant is at least one of pentaerythritol stearate and ethylene bis-stearamide.
[0011] Furthermore, the maleic anhydride graft compatibilizer is a maleic anhydride-grafted ethylene-octene copolymer with a maleic anhydride grafting rate of 0.5-1.5 wt%.
[0012] Furthermore, the preparation process of the talc and boehmite composite modified powder is as follows: 100 parts of talc powder and 30-50 parts of boehmite powder are dried at 100-140℃ for 2-5 h; wherein the talc powder has a particle size of 1-5 μm and the boehmite has a particle size of 0.2-2 μm; the dried talc powder and boehmite powder are mixed to obtain an inorganic composite powder; 1.5-3.5 parts of isopropyltris(dioctylpyrophosphate)titanate and 1.3-2.0 parts of γ-glycidyl etheroxypropyltrimethoxysilane are added to 30-40 parts of an alcohol solvent and stirred to disperse, obtaining a composite modified liquid; the inorganic composite powder is added to a high-speed mixer and heated to 80-120℃, and the composite modified liquid is sprayed onto the inorganic composite powder under stirring conditions, and mixing is continued for 20-60 min, followed by drying at 90-100℃ for 1-3 hours. h, after crushing and sieving, yields a composite modified powder of talc and boehmite.
[0013] To better achieve the objectives of this invention, this invention also provides a manufacturing process for a lithium battery cover plate, comprising the following steps: 1. After melting aluminum ingots, Mg, Si, Cu, Mn, Sc, Zr, Ti, B, and Nb elements are added sequentially. The mixture is then smelted under a protective atmosphere, refined, degassed, and slag-removed before casting to obtain aluminum alloy ingots. The aluminum alloy ingots are then subjected to homogenization, hot rolling, solution treatment, and aging treatment to obtain aluminum alloy sheets. Finally, the sheets are stamped, machined, or cut to produce metal parts that surround and are mounted on the outside of plastic parts. 2. The plastic raw material is added to a twin-screw extruder for melt blending, extrusion, cooling and pelletizing to obtain modified plastic pellets; Third, using insert injection molding, the metal parts are first degreased, cleaned, roughened and dried. The treated metal parts are then placed into the positioning cavity of the injection mold. Modified plastic granules are melted and plasticized at 320-340℃ and injected into the mold cavity, so that the plastic melt fills the limiting groove inside the metal parts. After cooling and solidification, an integrally molded lithium battery cover plate with mechanical interlocking between the plastic parts and the metal parts is obtained.
[0014] Furthermore, in step one, the homogenization treatment temperature is 500-560℃, and the holding time is 4-8h; the solution treatment temperature is 520-560℃, and the holding time is 0.5-3h; the aging treatment temperature is 160-190℃, and the holding time is 4-8h.
[0015] Furthermore, in step two, the temperature in each zone of the twin-screw extruder is 280-340℃; the screw speed is 150-350 r / min.
[0016] Furthermore, in step three, the mold temperature is 120-160℃, the injection pressure is 70-100MPa, and the holding time is 10-30s.
[0017] Compared with existing technologies, the advantages of this invention are as follows: 1. This invention uses a plastic component and a metal component surrounding the plastic component to form a lithium battery cover. The metal component is used for welding and fixing to the battery casing, while the plastic component provides internal insulation and electrolyte sealing. Through this structure, the welding support function and insulation sealing function, which are simultaneously performed by the metal component in traditional metal cover plates, are separated. This allows the metal component to primarily meet the requirements for welding strength and structural support, while the plastic component primarily meets the requirements for insulation and electrolyte sealing. This reduces the risk of short circuits caused by insulation component misalignment, damage, or aging, thus improving the safety of the battery cover.
[0018] 2. This invention employs isopropyltris(dioctylpyrophosphate)titanate and γ-glycidyl etheroxypropyltrimethoxysilane to perform composite surface modification of talc and boehmite powder. The titanate coupling agent can improve the organic compatibility of the inorganic powder surface and enhance its dispersion in the resin matrix; the epoxy silane coupling agent can strengthen the interfacial bonding between the inorganic powder and polar resins such as semi-aromatic polyamides and polyetherimide resins. The composite-modified powder is more uniformly dispersed in the PA10T / PPS / PEI resin system, and the tensile strength, electrolyte resistance, and insulation stability after thermal cycling of the plastic parts are all improved.
[0019] 3. This invention employs an insert injection molding method, whereby molten plastic fills the limiting groove inside the metal part, and after cooling and solidification, a mechanical interlocking connection is formed between the plastic part and the metal part. Alternatively, at least two circumferentially extending annular limiting grooves can be provided on the inner side of the metal part, with adjacent annular limiting grooves spaced apart along the height direction of the metal part. This increases the length of the interface sealing path, reduces the risk of electrolyte or gas leakage along the interface, and improves the long-term sealing reliability of the cover plate. Detailed Implementation
[0020] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.
[0021] Example 1: A manufacturing process for a lithium battery cover plate, comprising the following steps: I. Preparation of metal parts After melting aluminum ingots, Mg, Si, Cu, Mn, Sc, Zr, Ti, B, and Nb elements are added sequentially. The mixture is then smelted under a protective atmosphere, refined, degassed, and slag-removed before casting to obtain an aluminum alloy ingot. The aluminum alloy ingot undergoes homogenization, hot rolling, solution treatment, and aging treatment to obtain aluminum alloy sheets. These sheets are then stamped, machined, or cut to produce metal parts that surround and are mounted on the outside of plastic parts. The homogenization treatment temperature is 500℃, held for 8 hours; the solution treatment temperature is 520℃, held for 3 hours; and the aging treatment temperature is 160℃, held for 8 hours.
[0022] The metal component comprises the following raw materials by weight percentage: Mg: 0.50%, Si: 0.40%, Fe: 0.11%, Cu: 0.10%, Mn: 0.06%, Sc: 0.05%, Zr: 0.02%, Ti: 0.03%, B: 0.001%, Nb: 0.03%, with the balance being Al and unavoidable impurities.
[0023] II. Preparation of Talc and Boehmite Composite Modified Powder 100 parts of talc powder and 30 parts of boehmite powder were dried at 140℃ for 2 h; wherein the talc powder had a particle size of 5 μm and the boehmite had a particle size of 0.2 μm; the dried talc powder and boehmite powder were mixed to obtain an inorganic composite powder; 3.5 parts of isopropyltris(dioctylpyrophosphate)titanate and 1.3 parts of γ-glycidyl etheroxypropyltrimethoxysilane were added to 40 parts of an alcohol solvent (e.g., ethanol) and stirred to disperse to obtain a composite modification liquid; the inorganic composite powder was added to a high-speed mixer and heated to 80℃. Under stirring conditions, the composite modification liquid was sprayed into the inorganic composite powder and mixed for another 60 min. Then it was dried at 90℃ for 3 h. After pulverization and sieving, the talc and boehmite composite modified powder was obtained.
[0024] III. Preparation of Modified Plastic Granules Weigh out 100 parts of semi-aromatic polyamide (preferably PA10T), 15 parts of polyphenylene sulfide (PPS), 18 parts of polyetherimide resin (PEI), 0.5 parts of maleic anhydride-grafted ethylene-octene copolymer (POE-g-MAH), 8 parts of talc and boehmite composite modified powder, 0.3 parts of carbodiimide, 0.8 parts of antioxidant 1098, and 0.2 parts of ethylene bis-stearamide. The maleic anhydride grafting rate of the maleic anhydride-grafted ethylene-octene copolymer is 1.5 wt%. Add the plastic raw materials to a twin-screw extruder for melt blending, extrusion, cooling, and pelletizing to obtain modified plastic granules. The twin-screw extruder has a gradually increasing temperature from the feeding section to the die head, with the temperatures in each zone being 280-300℃, 295-315℃, 305-325℃, 315-335℃, and 320-340℃ respectively. The die head temperature is 320-340℃, and the screw speed is 350 r / min.
[0025] IV. Using insert injection molding, the metal parts are first degreased, cleaned, roughened and dried. The treated metal parts are then pre-placed into the positioning cavity of the injection mold. Modified plastic granules are melted and plasticized at 340℃ and injected into the mold cavity. The mold temperature is 120℃, the injection pressure is 100MPa and the holding time is 10s. The plastic melt fills the limiting groove inside the metal part. After cooling and solidification, an integrally molded lithium battery cover plate with mechanical interlocking between the plastic part and the metal part is obtained.
[0026] Example 2: A manufacturing process for a lithium battery cover plate, comprising the following steps: I. Preparation of metal parts After melting aluminum ingots, Mg, Si, Cu, Mn, Sc, Zr, Ti, B, and Nb elements are added sequentially. The mixture is then smelted under a protective atmosphere, refined, degassed, and slag-removed before casting to obtain an aluminum alloy ingot. The aluminum alloy ingot undergoes homogenization, hot rolling, solution treatment, and aging treatment to obtain aluminum alloy sheets. These sheets are then stamped, machined, or cut to produce metal parts that surround and are mounted on the outside of plastic parts. The homogenization treatment temperature is 560℃, held for 4 hours; the solution treatment temperature is 560℃, held for 0.5 hours; and the aging treatment temperature is 190℃, held for 4 hours.
[0027] The metal component comprises the following raw materials by weight percentage: Mg: 0.80%, Si: 0.20%, Fe: 0.22%, Cu: 0.05%, Mn: 0.12%, Sc: 0.03%, Zr: 0.05%, Ti: 0.01%, B: 0.005%, Nb: 0.01%, with the balance being Al and unavoidable impurities.
[0028] II. Preparation of Talc and Boehmite Composite Modified Powder 100 parts of talc powder and 50 parts of boehmite powder were dried at 100℃ for 5 h, respectively; wherein the talc powder had a particle size of 1 μm and the boehmite had a particle size of 2 μm; the dried talc powder and boehmite powder were mixed to obtain an inorganic composite powder; 1.5 parts of isopropyltris(dioctylpyrophosphate)titanate and 2.0 parts of γ-glycidyl etheroxypropyltrimethoxysilane were added to 30 parts of an alcohol solvent (e.g., ethanol) and stirred to disperse to obtain a composite modified liquid; the inorganic composite powder was added to a high-speed mixer and heated to 120℃, and the composite modified liquid was sprayed into the inorganic composite powder under stirring conditions, and the mixture was continued to be mixed for 20 min, and then dried at 95℃ for 1 h. After pulverization and sieving, the talc and boehmite composite modified powder was obtained.
[0029] III. Preparation of Modified Plastic Granules Weigh out 100 parts of semi-aromatic polyamide (preferably PA10T), 22 parts of polyphenylene sulfide, 5 parts of polyetherimide resin, 3 parts of maleic anhydride-grafted ethylene-octene copolymer (POE-g-MAH), 2 parts of talc and boehmite composite modified powder, 1.5 parts of carbodiimide, 0.2 parts of antioxidant 168, and 1 part of pentaerythritol stearate. The maleic anhydride grafting rate of the maleic anhydride-grafted ethylene-octene copolymer is 0.5 wt%. Add the plastic raw material to a twin-screw extruder for melt blending, extrusion, cooling, and pelletizing to obtain modified plastic pellets. The twin-screw extruder has a gradually increasing temperature from the feeding section to the die head, with the temperatures in each zone being 280-300℃, 295-315℃, 305-325℃, 315-335℃, and 320-340℃ respectively. The die head temperature is 320-340℃, and the screw speed is 350 r / min.
[0030] Fourth, using insert injection molding, the metal parts are first degreased, cleaned, roughened and dried. The treated metal parts are then pre-placed into the positioning cavity of the injection mold. Modified plastic granules are melted and plasticized at 320℃ and injected into the mold cavity. The mold temperature is 160℃, the injection pressure is 70MPa, and the holding time is 30s. This allows the plastic melt to fill the limiting groove inside the metal part. After cooling and solidification, an integrally molded lithium battery cover plate with mechanical interlocking between the plastic part and the metal part is obtained.
[0031] Example 3: A manufacturing process for a lithium battery cover plate, comprising the following steps: I. Preparation of metal parts After melting aluminum ingots, Mg, Si, Cu, Mn, Sc, Zr, Ti, B, and Nb elements are added sequentially. The mixture is then smelted under a protective atmosphere, refined, degassed, and slag-removed before casting to obtain an aluminum alloy ingot. The aluminum alloy ingot undergoes homogenization, hot rolling, solution treatment, and aging treatment to obtain aluminum alloy sheets. These sheets are then stamped, machined, or cut to produce metal parts that surround and are mounted on the outside of plastic parts. The homogenization treatment temperature is 550℃, held for 6 hours; the solution treatment temperature is 540℃, held for 1.5 hours; and the aging treatment temperature is 180℃, held for 5.5 hours.
[0032] The metal component comprises the following raw materials by weight percentage: Mg: 0.65%, Si: 0.26%, Fe: 0.14%, Cu: 0.08%, Mn: 0.08%, Sc: 0.04%, Zr: 0.04%, Ti: 0.02%, B: 0.003%, Nb: 0.02%, with the balance being Al and unavoidable impurities.
[0033] II. Preparation of Talc and Boehmite Composite Modified Powder 100 parts of talc powder and 45 parts of boehmite powder were dried at 125℃ for 3.5 h; wherein the talc powder had a particle size of 3 μm and the boehmite had a particle size of 1 μm. The dried talc powder and boehmite powder were mixed to obtain an inorganic composite powder. 2.5 parts of isopropyltris(dioctylpyrophosphate)titanate and 1.6 parts of γ-glycidyl etheroxypropyltrimethoxysilane were added to 32 parts of an alcohol solvent (e.g., ethanol) and stirred to disperse, thus obtaining a composite modified liquid. The inorganic composite powder was added to a high-speed mixer and heated to 96℃. Under stirring conditions, the composite modified liquid was sprayed into the inorganic composite powder and mixed for another 40 min. Then, it was dried at 100℃ for 2 h. After pulverization and sieving, the talc and boehmite composite modified powder was obtained.
[0034] III. Preparation of Modified Plastic Granules Weigh out 100 parts of semi-aromatic polyamide (preferably PA10T), 18 parts of polyphenylene sulfide, 15 parts of polyetherimide resin, 1.8 parts of maleic anhydride-grafted ethylene-octene copolymer (POE-g-MAH), 4.3 parts of talc and boehmite composite modified powder, 0.8 parts of carbodiimide, 0.6 parts of antioxidant 1098, and 0.6 parts of pentaerythritol stearate. The maleic anhydride grafting rate of the maleic anhydride-grafted ethylene-octene copolymer is 1.2 wt%. Add the plastic raw material to a twin-screw extruder for melt blending, extrusion, cooling, and pelletizing to obtain modified plastic granules. The twin-screw extruder has a gradually increasing temperature from the feeding section to the die head, with the temperatures in each zone being 280-300℃, 295-315℃, 305-325℃, 315-335℃, and 320-340℃ respectively. The die head temperature is 320-340℃, and the screw speed is 250 r / min.
[0035] Fourth, using insert injection molding, the metal parts are first degreased, cleaned, roughened and dried. The treated metal parts are then pre-placed into the positioning cavity of the injection mold. Modified plastic granules are melted and plasticized at 325℃ and injected into the mold cavity. The mold temperature is 145℃, the injection pressure is 85MPa, and the holding time is 22s. The plastic melt fills the limiting groove inside the metal part. After cooling and solidification, an integrally molded lithium battery cover plate with mechanical interlocking between the plastic part and the metal part is obtained.
[0036] Comparative Example 1: Unlike Example 3, the talc and boehmite composite modified powder was replaced with an equal amount of unmodified talc powder and boehmite powder blend, and isopropyltris(dioctylpyrophosphate)titanate and γ-glycidyl etheroxypropyltrimethoxysilane were not used for surface modification. The other raw materials and process conditions were the same as in Example 3.
[0037] The following properties of the plastic parts prepared in Comparative Examples 1-3 and Comparative Example 1 are compared: Tensile strength GB / T 1040.2-2022.
[0038] Water absorption rate of plastic parts GB / T 1034-2008.
[0039] Mass change rate after immersion in electrolyte (GB / T 11547-2008)
[0040] Insulation resistance after thermal cycling: GB / T 2423.22-2012, GB / T 31838.2-2019.
[0041]
[0042] It can be seen that the talc and boehmite composite modified powder used in Examples 1-3, after being surface-treated with isopropyltris(dioctylpyrophosphate)titanate and γ-glycidyl etheroxypropyltrimethoxysilane, can significantly improve the dispersibility and interfacial bonding strength of inorganic powders in the PA10T / PPS / PEI resin system. Compared with Comparative Example 1, which uses unmodified powder, the examples exhibit higher tensile strength, lower water absorption, lower electrolyte immersion mass change rate, and higher insulation resistance after thermal cycling, indicating that the plastic part system of the present invention is more suitable for the insulating and sealing structure of lithium battery cover plates.
[0043] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A lithium battery cover, characterized in that, It includes a plastic part and a metal part surrounding and disposed on the outside of the plastic part, the plastic part being used to provide internal insulation and electrolyte sealing, and the metal part being used to weld and fix it to the battery casing; The plastic part comprises the following raw materials in parts by weight: 100 parts of semi-aromatic polyamide, 15-22 parts of polyphenylene sulfide, 5-18 parts of polyetherimide resin, 0.5-3 parts of maleic anhydride graft compatibilizer, 2-8 parts of talc and boehmite composite modified powder, 0.3-1.5 parts of hydrolysis resistant agent, 0.2-0.8 parts of antioxidant, and 0.2-1 parts of lubricant.
2. The lithium battery cover plate according to claim 1, characterized in that, The metal component comprises the following raw materials by weight percentage: Mg: 0.50-0.80%, Si: 0.20-0.40%, Fe: 0.11-0.22%, Cu: 0.05-0.10%, Mn: 0.06-0.12%, Sc: 0.03-0.05%, Zr: 0.02-0.05%, Ti: 0.01-0.03%, B: 0.001-0.005%, Nb: 0.01-0.03%, with the balance being Al and unavoidable impurities.
3. The lithium battery cover plate according to claim 1, characterized in that, The hydrolysis-resistant agent is carbodiimide; the antioxidant is at least one of antioxidant 1098 and antioxidant 168.
4. The lithium battery cover plate according to claim 1, characterized in that, The lubricant is at least one of pentaerythritol stearate and ethylene bis-stearamide.
5. The lithium battery cover plate according to claim 1, characterized in that, The maleic anhydride graft compatibilizer is a maleic anhydride-grafted ethylene-octene copolymer with a maleic anhydride grafting rate of 0.5-1.5 wt%.
6. The lithium battery cover plate according to claim 1, characterized in that, The preparation process of the talc and boehmite composite modified powder is as follows: 100 parts of talc powder and 30-50 parts of boehmite powder are dried at 100-140℃ for 2-5 h; wherein the talc powder has a particle size of 1-5 μm and the boehmite has a particle size of 0.2-2 μm; the dried talc powder and boehmite powder are mixed to obtain an inorganic composite powder; 1.5-3.5 parts of isopropyltris(dioctylpyrophosphate)titanate and 1.3-2.0 parts of γ-glycidyl etheroxypropyltrimethoxysilane are added to 30-40 parts of an alcohol solvent and stirred to disperse, obtaining a composite modified liquid; the inorganic composite powder is added to a high-speed mixer and heated to 80-120℃, and the composite modified liquid is sprayed onto the inorganic composite powder under stirring conditions, and mixing is continued for 20-60 min, followed by drying at 90-100℃ for 1-3 hours. h, after crushing and sieving, yields a composite modified powder of talc and boehmite.
7. A manufacturing process for a lithium battery cover plate according to any one of claims 1-6, characterized in that, Includes the following steps:
1. After melting aluminum ingots, Mg, Si, Cu, Mn, Sc, Zr, Ti, B, and Nb elements are added sequentially. The mixture is then smelted under a protective atmosphere, refined, degassed, and slag-removed before casting to obtain aluminum alloy ingots. The aluminum alloy ingots are then subjected to homogenization, hot rolling, solution treatment, and aging treatment to obtain aluminum alloy sheets. Finally, the sheets are stamped, machined, or cut to produce metal parts that surround and are mounted on the outside of plastic parts.
2. The plastic raw material is added to a twin-screw extruder for melt blending, extrusion, cooling and pelletizing to obtain modified plastic pellets; 3. Using insert injection molding, the surface of the metal part is first treated, and the treated metal part is pre-placed into the positioning cavity of the injection mold; the modified plastic granules are melted and plasticized at 320-340℃ and then injected into the mold cavity, so that the plastic melt fills the limiting groove on the inner side of the metal part. After cooling and solidification, an integrally molded lithium battery cover plate with mechanical interlocking between the plastic part and the metal part is obtained.
8. The manufacturing process of the lithium battery cover plate according to claim 7, characterized in that, In step one, the homogenization treatment temperature is 500-560℃, and the holding time is 4-8h; the solution treatment temperature is 520-560℃, and the holding time is 0.5-3h; the aging treatment temperature is 160-190℃, and the holding time is 4-8h.
9. The manufacturing process of the lithium battery cover plate according to claim 7, characterized in that, In step two, the temperature in each zone of the twin-screw extruder is 280-340℃; the screw speed is 150-350 r / min.
10. The manufacturing process of the lithium battery cover plate according to claim 7, characterized in that, In step three, the mold temperature is 120-160℃, the injection pressure is 70-100MPa, and the holding time is 10-30s.